2022
DOI: 10.3390/horticulturae8080678
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality and Production of Philodendron Plants Using Nanoparticles and Humic Acid

Abstract: A pot experiment was conducted during the 2019/2020 and 2020/2021 seasons to evaluate the effect of silver nanoparticles (SNPs), iron nanoparticles (FeNPs), zinc nanoparticles (ZnNPs), and nitrogen, phosphorus, and potassium nanoparticles (NPK NPs) and humic acid (HA) in improving the growth of Philodendron plants. Our findings indicated that the highest increase in plant height and leaf width was recorded with 60 mg/L SNPs. Additionally, the highest values in the number of leaves plant−1 were recorded with 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Si reduces transpiration due to accumulation in the tissues of cuticles (Keller et al, 2015). The results are in accordance with those of El-Shawa et al (2022) found that the highest increase in plant height, leaf width, stem diameter and leaves the number of philodendron plants duo to 60mg/l AgNPs in compression to control, FeNPs and ZnNPs. And Ismail et al (2022) revealed that SiNPs application at the rate of 3 mM caused a significant increase in plant height, fresh and dry weights and total yield of Pisum sativum plant when compared to the control.…”
Section: Resultssupporting
confidence: 88%
“…Si reduces transpiration due to accumulation in the tissues of cuticles (Keller et al, 2015). The results are in accordance with those of El-Shawa et al (2022) found that the highest increase in plant height, leaf width, stem diameter and leaves the number of philodendron plants duo to 60mg/l AgNPs in compression to control, FeNPs and ZnNPs. And Ismail et al (2022) revealed that SiNPs application at the rate of 3 mM caused a significant increase in plant height, fresh and dry weights and total yield of Pisum sativum plant when compared to the control.…”
Section: Resultssupporting
confidence: 88%
“…The application of nano silica and melatonin individually or in combination led to an increased membrane stability, which induced the plant defenses by adjusting the enzymes activity, total phenolic compounds and proline content, which scavenged the ROS and protected the cells of the pea plants from oxidative damage under salt stress compared to the stressed pea plants that did not receive treatments. The helpful effect of SNPs on enzyme regulation was also recorded by Mukarram et al [85], El-Shawa et al [103] and Khedr et al [43]. SiNPs can regulate CAT, APX and SOD activities and the AsA-GSH cycle, which improves the defense system.…”
Section: Discussionmentioning
confidence: 74%
“…Consequently, the application of Si-NPs could serve as a useful tool for increasing rice's tolerance to oxidative stress by bolstering its enzymatic defences against ROS. In this regard, (Mukarram et al, 2022) (El-Shawa et al, 2022) (Elshayb et al, 2021) reported that the use of Si-NPs increased antioxidant enzymes against oxidative stress. Grain yield is the ultimate product of the physiological processes of different stages of plant development.…”
Section: Discussionmentioning
confidence: 99%